Efficacy of seventh generation bonding agents as desensitizers in patients with dentin hypersensitivity: a randomized clinical trial - Sumaiya Shabbir; Shahbaz Ahmed; Syed Jaffar Abbas Zaidi; Sania Riaz; Huma Sarwar; Muhammad Taqi; Zia ur Rahman Khan (BMC, 2024)
Abstract Background Dentin hypersensitivity (DH) is one of the most challenging and persistent dental complaints characterized by transient, intense pain triggered by various stimuli. It affects a significant portion of the global population, predominantly those aged 20-40. This study aims to evaluate the desensitizing efficacy of seventh-generation dentin bonding agents (Single Bond Universal by 3 M ESPE and Xeno-V + by Dentsply) against a control group using Bifluorid 12 by Voco in mitigating DH within a month of the follow-up period. Methods This was a single-center, parallel-group, double-blind, controlled randomized clinical trial conducted at Dow University of Health Sciences, Karachi, Pakistan. A total of 105 patients with DH were allocated into three groups for this study. The patients were divided into three groups (Single Bond Universal by 3 M ESPE and Xeno-V + by Dentsply) and the control group containing fluoride varnish (Bifluorid 12 by Voco). Discomfort Interval Scale scores and Schiff Cold Air Sensitivity Scale scores were recorded at baseline, immediately after the intervention, after 01 weeks, and after 01 month. Results All the materials demonstrated a statistically significant reduction in discomfort and sensitivity (DIS scores p-value 0.01) immediately after 01 week and over a period of 01 month after treatment compared with the baseline scores before application, with no single material proving superior over the one-month observation period. The study also provided insights into dental hygiene practices, with a significant majority using a toothbrush and sensitivity patterns, with cold stimuli being the most common cause of sensitivity. Conclusion The study demonstrates that Single Bond Universal, Xeno V+, and Bifluorid 12 are equally effective in reducing dentin hypersensitivity, with no distinct superiority observed over a one-month period. The findings highlight the potential of fluoride varnishes as a less technique-sensitive and cost-effective option for treating DH, offering valuable insights for future research and clinical practice. Trial registration NCT04225247 ( https://clinicaltrials.gov/study/NCT04225247 ), Date of Registration: 13/01/2020. (Retrospectively registered).